2017
DOI: 10.9790/0837-2206060106
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Parenting Pattern to Moral Formation and Student’s Class XI Learning Outcomes in Christian Religious Education at Vocational High School (SMK) Immanuel Medan In School Year 2015/2016

Abstract: Abstract:This study aims to find out the significant contribution of parenting pattern according to repetition 6: 1-9 on moral formation of students, and to know the significant contribution of parenting pattern according to repetition 6: 1-9 to the result of student's learning outcome of Christian Education Subject at SMK Immanuel Medan. The population of this study were all students of class XI SMK Immanuel Medan which amounted to 190 people, and the number of samples included in this study were (25% × 190) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Therefore, when high levels of conflict are seen in family relationships, it means that members have experienced a lack of coordination (Zhou et al, 2006). Studies have shown that parents play a very important role in creating a balanced harmony in family relationships (Sitepu, 2018). Parents with coordination not only create peace and comfort for their children but also ensure they receive proper parental guidance and support (Sitepu, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, when high levels of conflict are seen in family relationships, it means that members have experienced a lack of coordination (Zhou et al, 2006). Studies have shown that parents play a very important role in creating a balanced harmony in family relationships (Sitepu, 2018). Parents with coordination not only create peace and comfort for their children but also ensure they receive proper parental guidance and support (Sitepu, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that parents play a very important role in creating a balanced harmony in family relationships (Sitepu, 2018). Parents with coordination not only create peace and comfort for their children but also ensure they receive proper parental guidance and support (Sitepu, 2018). In line with research findings, Di Fabio and Tsuda (2018) in their research on human multi-dimensional harmonization, consider selfharmonization to have a relational nature that includes harmonization with oneself, with others, with communicative contexts, and with nature (the whole universe).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fokus utama dunia Pendidikan adalah manusia yaitu peserta didik yang didorong untuk meningkatkan kualitas hidupnya. Peserta didik adalah anggota masyarakat yang berusaha mengembangkan potensi diri melalui proses pembelajaran yang tersedia pada jalur, jenjang, dan jenis pendidikan tertentu (Sitepu, 2017). Peserta didik adalah salah satu komponen pendidikan yang penting karena mereka adalah yang akan menerima pembelajaran dari pendidik dan juga akan mengimplementasikan pengajaran-pengajaran tersebut.…”
Section: Unit Penelitian Dan Pengabdian Masyarakat Politeknikunclassified